Introduction. Access to the gland: Round Table Thyroidectomies coordinator Lorenzo Mérola - Mérola, Lorenzo (Cirugía del Uruguay, 1973)
The author describes approach to cervical goiter. and analyzes all inherent aspects starting by position of patient on operating table and up to type of anesthesia employed. He then considers the different incisions possible, as well as the different manners of cutting the cutaneous flap, and finishes with anatomical and functional considerations on useful surgical space and infrahyoid muscles.